The effectiveness of back rolling massage on the speed of breastfeeding in post-partum mothers in the independent practice of midwives in Baturaja city - Anggraini, Helni; Yunola, Satra; Darma, Ika Yulia; Zaimy, Silvi (International Journal Of Community Medicine And Public Health, 2022)
Background: Exclusive breastfeeding during the first 0-6 months has a role for optimal growth and motor development of children. Indonesia has an exclusive breastfeeding target of 80%, but the achievement target of the exclusive breastfeeding program in South Sumatra is 47%. One of the factors causing the low coverage of exclusive breastfeeding is due to the insufficient volume of breast milk for the baby’s intake so that the mother provides additional formula milk to her baby. Back rolling massage, one of the non-pharmacological efforts to help the production of breast milk. This study aimed to determine the effectiveness of back rolling massage on the rate of expenditure of breast milk in postpartum mothers in independent practice midwife Baturaja. Methods: It was quantitative research with cross sectional design. The study was conducted from August to September 2022 in the independent midwife practice of Baturaja city. A total of 60 samples were used in this study with purposive sampling technique. Data were analysed in univariate and bivariate. The chi-square test was used in this study. Results: The results showed, as many as 47 people (78.3%) who did back rolling massage, there were 42 mothers (89.4%) who experienced accelerated breastfeeding. Based on statistical tests obtained p value of 0.000 (p<0.05) with the value of odds ratio (OR) of 2.106. Conclusions: Back rolling massage is effective in accelerating the expulsion of breast milk for post partum mothers.